2023
DOI: 10.3390/electronics12081775
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Fluency Assessment Method for Spontaneous Speech without Reference Text

Abstract: The automatic fluency assessment of spontaneous speech without reference text is a challenging task that heavily depends on the accuracy of automatic speech recognition (ASR). Considering this scenario, it is necessary to explore an assessment method that combines ASR. This is mainly due to the fact that in addition to acoustic features being essential for assessment, the text features output by ASR may also contain potentially fluency information. However, most existing studies on automatic fluency assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…PSC-PS-DF consists of propositional speaking files for the Mandarin Proficiency Test (Putonghua Shuiping Ceshi, PSC). Previous work has shown that, due to the nature of Chinese propositional speaking, which requires the speaker to freely describe a topic for three minutes without any reference text, the speech files contain a large number of disfluent features, such as "um", "ah", and "uh" interjections, blocks, prolongations, and repetition, but such disfluent features are rarely marked and used in research [55]. In this study, disfluent features were annotated in Chinese propositional speaking data to obtain spontaneously spoken disfluent features in Chinese for the detection of disfluent Chinese-language speech.…”
Section: Psc-ps-dfmentioning
confidence: 99%
“…PSC-PS-DF consists of propositional speaking files for the Mandarin Proficiency Test (Putonghua Shuiping Ceshi, PSC). Previous work has shown that, due to the nature of Chinese propositional speaking, which requires the speaker to freely describe a topic for three minutes without any reference text, the speech files contain a large number of disfluent features, such as "um", "ah", and "uh" interjections, blocks, prolongations, and repetition, but such disfluent features are rarely marked and used in research [55]. In this study, disfluent features were annotated in Chinese propositional speaking data to obtain spontaneously spoken disfluent features in Chinese for the detection of disfluent Chinese-language speech.…”
Section: Psc-ps-dfmentioning
confidence: 99%